The Dynamics of Tafsir bi al-Ma’thur and Tafsir bi al-Ra’y in the Mutaakhkhirin Period: A Methodological and Epistemological Study - Aji Muhammad Ibrahim (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2026)
The development of Qur’anic exegesis reflects the dynamic interaction between revelation and the evolving intellectual, social, and political contexts of Muslim societies. The mutaakhkhirin (post-classical) period, spanning approximately the 4th to 12th centuries Hijri, represents a critical phase in this trajectory, marked by increasing methodological complexity and epistemological expansion. This study aims to analyze the historical dynamics, methodological transformation, and epistemological configuration of tafsir during this period. Employing a qualitative library research approach, the study draws on primary exegetical works and relevant secondary literature, analyzed through historical, methodological, and epistemological frameworks. The findings demonstrate that the development of tafsir in the mutaakhkhirin period cannot be adequately understood as a linear shift from tafsir bi al-ma’thur to tafsir bi al-ra’y. Rather, it reflects an integrative process in which transmitted knowledge and rational inquiry are systematically combined. This integration is further reinforced by the incorporation of linguistic, philosophical, and scientific disciplines, resulting in more analytical, structured, and context-sensitive interpretations. The study argues that this period represents a maturity in the evolution of tafsir, characterized by the reconfiguration of epistemic authority and the emergence of a synthetic interpretive framework. These findings contribute to a more nuanced understanding of post-classical exegesis and highlight its relevance for modern Qur’anic interpretation.